The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/ac301091m
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Comprehensiveness and Sensitivity of Sheathless Capillary Electrophoresis–Tandem Mass Spectrometry for Proteomic Analysis

Abstract: We describe a solid phase microextraction (SPME), multistep elution, transient isotachophoresis (tITP) CE-MS/MS procedure which employs a high sensitivity porous ESI sprayer for the proteomic analysis of a moderately complex protein mixture. In order to improve comprehensiveness and sensitivity over a previously reported proteomic application of the ESI sprayer, we evaluated preconcentration with SPME and multistep elution prior to tITP stacking and CE separation. To maximize separation efficiency we primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
160
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 48 publications
(104 reference statements)
5
160
0
Order By: Relevance
“…Similar complementary peptide identification was found in recent CE and nano-LC studies by our group and other researchers (32,39,58). CE shows a clear bias toward basic, hydrophilic peptides of low molecular mass.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar complementary peptide identification was found in recent CE and nano-LC studies by our group and other researchers (32,39,58). CE shows a clear bias toward basic, hydrophilic peptides of low molecular mass.…”
Section: Discussionsupporting
confidence: 87%
“…CE shows a clear bias toward basic, hydrophilic peptides of low molecular mass. Additionally, the Yates Lab attributed gains in sensitivity to lower noise levels with CE, illustrated by better signal-to-noise ratios of peptide precursor ions and associated higher XCorr values of identified peptides relative to LC (58). These trends may be also explained by the difference in electrospray conditions between the methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, since only the porous end of the separation capillary is housed in the reservoir, the passage of ions from the reservoir through the pores in the separation capillary is achieved without dilution of the BGE. A number of groups have utilized this interface in proteomics experiments [1, [66][67][68][69][70]. The interface is sold commercially via SCIEX (Toronto, Canada) and marketed for CZE-MS applications as a part of SCIEX's CESI platform.…”
mentioning
confidence: 99%
“…As with FASS and PHJ, major application field of tITP-CE-MS includes proteomics [82][83][84][85][86][87][88]. Wang et al reported combination of reverse-phase solid phase microextraction with tITP-CZE-nanoESI-MS [82].…”
mentioning
confidence: 99%
“…Wang et al reported combination of reverse-phase solid phase microextraction with tITP-CZE-nanoESI-MS [82]. They succeeded in identification of up to 370 proteins from 50 ng of Xenopus laevis proteins.…”
mentioning
confidence: 99%